2018
DOI: 10.18240/ijo.2018.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of sodium hyaluronate temporarily elevates the tear film lipid layer thickness in dry eye patients with lipid deficiency

Abstract: SH eye drops induce a short-term increase in LLT of patients with lipid deficiency. A low concentration of artificial tears have a stronger effect than a high concentration of artificial tears on the increase in LLT. In comparison, SH eye drops induce a transient and slight decrease in LLT of patients without lipid deficiency. A low concentration of artificial tears might be better for patients with lipid deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, Szegedi et al found that a single HA application via eye drops may increase TFT in patients with dry eye syndrome [ 19 ]. Moreover, in vivo studies confirmed the increase in the thickness of the tear film (from 60 to 75 nm) induced by 0.1% HA solution in patients with lipid deficiency as a consequence of dry eye syndrome [ 20 ].…”
Section: Introductionmentioning
confidence: 92%
“…In addition, Szegedi et al found that a single HA application via eye drops may increase TFT in patients with dry eye syndrome [ 19 ]. Moreover, in vivo studies confirmed the increase in the thickness of the tear film (from 60 to 75 nm) induced by 0.1% HA solution in patients with lipid deficiency as a consequence of dry eye syndrome [ 20 ].…”
Section: Introductionmentioning
confidence: 92%
“… 13 , 15 However, ultrasonic moisture glasses can rapidly raise humidity to 90%. The glasses may prolong TBUT without dynamic changes in the tear film, including in the lipid layer, 20 , 21 as observed during usage of artificial tears. Thus, patients may not experience dryness or a decrease in visual acuity, which occurs just after using eye drops.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of mucin-like polymers for the performance of TFLL was confirmed in vivo by the capability of a 0.1% HA-induced increase (from <60 to 75 nm) of TFLL thickness of lipid-deficient individuals [ 16 ], and by the comparable effect for >1 h post-instillation of 3% diquafosol ophthalmic solution (a drug promoting the rapid secretion of MUC5AC) on the TFLL in healthy human eyes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest that TFLL and endogenous and exogenous MMP may interact at the physiologically relevant timescale of seconds (H-bonding is a nanoseconds event), thus allowing for synchronous concerted action between the constituent of TFLL and AT. The impact of mucin-like polymers on TFLL was clinically demonstrated by the increase of the thickness of TFLL of lipid-deficient patients, from <60 to 75 nm, 15 min post-instillation of 0.1% HA [ 16 ], and by the similar effect of 3% diquafosol ophthalmic solution (strong MUC5AC secretatgogue) on the TFLL in healthy human eyes for more than 1 h post-instillation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%